EFFECTIVENESS OF TOTAL SUSPENDED SOLID (TSS) REMOVAL FOR COAL MINING WATER USING THE ELECTROCOAGULATION METHOD IN BATCH REACTORS USING IRON ELECTRODES - Oktaviani, Hanifah
Indonesia is a country that has considerable coal reserves with coal resources of 149.01 billion tons with South Sumatra and East Kalimantan being the provinces with the highest coal resources, accounting for 82% of the total coal resources in Indonesia. There are several types of mining methods, one of the most widely used is the open pit method. In the open pit coal mining process, issues were found with one of them being the turbidity. Turbidity in coal mine water is affected by soil due to erosion processes and mineral content in overburden which is transported by surface water flow. The turbidity that occurs is caused by the excavation of the open pit mine, making rainwater come in contact with the main wall. Thus, mud is formed which can increase turbidity levels. The concentration of Total Suspended Solids (TSS) due to this phenomenon reaches 5400 mg/L. This study aims to set aside TSS by electrocoagulation processing method using a batch system. In determining the maximum conditions for TSS removal, current variations of 0.5, 1, and 2 amperes and time variations of 15, 30, and 45 minutes were used, with 8 pairs of iron electrodes arranged monopolarly. From the experiment, the maximum TSS removal results were obtained at a current of 2 amperes and 30 minutes from an initial concentration of 5400 mg/L to 65.66 mg/L and TSS removal percent of 98.72%. There are other parameters that can affect the electrocoagulation process; those are pH, Total Dissolved Solid (TDS), and temperature, as well as an increase in pH from an initial value of 8 to 11, an increase in TDS concentration from an initial value of 320 mg/L to 477 mg/L, and an increase in temperature from 25? to 33.5?. After getting the results of electrocoagulation using iron electrodes, then a comparison of electrocoagulation with previous researchers regarding the removal of TSS using aluminum electrodes was carried out. Comparisons were made using statistical independet t tests the results showed that there was no significant difference between the iron and aluminum electrodes in the pH and efficiency TSS parameter. There were significant differences between iron and aluminum electrodes in the parameters measured TDS, temperature, and measured TSS. . In the measured TDS and measured TSS parameters, the electrocoagulation process using iron electrodes has a higher value than aluminum electrodes. In the TSS removal, there is no significant difference between the two electrodes (iron and aluminum). The cost of processing operations of electrocoagulation process is calculated on energy consumption and electrodes. The operating cost of electrocoagulation processing is calculated in terms of energy consumption which costs Rp 52/second or Rp 1,639,873,248/year.